Newborn screening for cystic fibrosis in Serbia: A pilot study. Issue 2 (27th February 2013) - Radivojevic, Danijela; Sovtic, Aleksandar; Minic, Predrag; Grkovic, Sanja; Guc‐Scekic, Marija; Lalic, Tanja; Miskovic, Marijana
Abstract Background We performed a pilot study of neonatal screening for cystic fibrosis (CF) in order to introduce it to the national screening program in Serbia. Methods Immunoreactive trypsinogen (IRT) concentrations were analyzed in dried blood spot samples. Patients were recalled for repeated measurements in case of high IRT levels. Persisting high IRT levels resulted in DNA testing for the 29 most common mutations in the CF transmembrane regulator (CFTR) gene (IRT/IRT/DNA method). Sweat chloride measurements and clinical assessment were further performed for newly diagnosed patients. Results Of 1000 samples, three were initially positive and were further analyzed for the presence of the most common CFTR mutations in the Serbian population. DNA analysis revealed two patients being homozygous for F508del mutation. One sample was false positive, as the genetic test proved to be negative and associated with normal sweat chloride concentration and unremarkable clinical presentation. Conclusions The results of our pilot study justified the expanding of the routine neonatal screening program in Serbia with CF. Data could be used in future in order to obtain accurate incidence of CF and carrier prevalence in our country.